منهج الإمام البیضاوی فی اختیاراته و ترجیحاته في التفسیر: دراسة تحلیلية وصفية - Mehmood Hasan; Musaab Iftikhar Durrani (البصيرة)
This research delves into the methodology and approach of Imam Al-Baydawi in his interpretative preferences within Tafsir. Focused on the theoretical and practical aspects, it aims to unravel the nuanced choices made by this renowned scholar. Imam Al-Baydawi's succinct and precise exegesis, highly regarded in the Islamic world, warrants a detailed investigation of his interpretative leanings. Despite his work's widespread influence, a gap exists in understanding his preferences. This study fills this void by meticulously examining and tracing Imam Al-Baydawi's interpretative tendencies, shedding light on his unique perspective. By exploring his approach, this research contributes to a deeper comprehension of Tafsir methodologies, offering insights valuable to both scholars and students in the field. Through a comprehensive analysis of Imam Al-Baydawi's interpretative preferences, this research seeks to elucidate the factors influencing his choices and shed light on the underlying principles guiding his exegesis. By considering the historical context, linguistic nuances, and theological frameworks prevalent during his time, this study seeks to gain a profound understanding of Imam Al-Baydawi's preferences and choices methodology in Tafsir.